ChemInform Abstract: The "One‐Pot" Synthesis of 4, 5‐Dihydrobenzo[g]indole and Its 1‐Vinyl Derivative from 1‐Tetralone, Hydroxylamine, and Dichloroethane in the System KOH—DMSO. Issue 12 (March 2015) - Ivanov, A. V.; Barnakova, V. S.; Mikhaleva, A. I.; Trofimov, B. A.
Abstract An environmentally‐friendly, fire‐safe, and explosion‐proof route to previously difficult accessible benzoindole derivatives is developed.